Regional Volume Tables of Six Native Tree Species of North-eastern Region, India - Sharma, R. P.; Jain, R. C. (Indian Forester, 1979)
Volume tables of six native tree species of north-eastern region of India have been prepared Grouping of species, based on similarity of bole form, has been adopted. Regression equations for total timber and total wood have been fitted. Models of the form V=a+b D2H and âˆšV=a+b D has been found to give the best fit. Using these models, tables for total timber and total wood have been prepared.